Buoyancy Analysis and Experimental Validation of Styrofoam Buoys on Amphibious Motorcycles - Nugroho, Akhamad Andriyan; Pranoto, Hadi (International Journal of Advanced Technology in Mechanical, Mechatronics and Materials, 2025)
Floods are the most frequent natural disasters that hit Indonesia and have a major impact on people's lives, especially in coastal areas such as Brebes which often face flash floods, so that conventional transportation systems are often completely paralyzed and hinder the evacuation process and distribution of aid. This research aims to develop amphibious motorcycles as an affordable alternative transportation solution in accordance with local conditions by utilizing local materials such as Styrofoam to overcome the limitations of access to similar technology in Indonesia. The research method used an experimental approach by designing and testing an amphibious motorcycle buoy made of used Styrofoam fruit boxes coated with plywood and fiber with dimensions of 179 cm × 37 cm × 38 cm per unit, mounted on Honda Beat motorcycles. The test was carried out through four loading variations ranging from no-load conditions to a maximum load of 223 kg, by measuring the depth of the dipped float to evaluate buoyancy based on the Archimedes principle. The results showed that the buoy was able to withstand a maximum load of 223 kg in stable conditions with a dip depth of 17 cm, resulting in an actual buoyancy force of 119 N although theoretical calculations showed a maximum capacity of 432 kg (4,233.6 N). The buoy system with a total weight of 24 kg (2 units) has a safety margin of 55.3% and is capable of operating with passengers up to 80 kg with maintained stability. This study validates that the design of the amphibious motorcycle has a strong theoretical basis and has been experimentally proven as an effective emergency transportation solution based on local materials for flood disaster mitigation in Indonesia.